ANALISIS PERBEDAAN JENIS BAHAN DAN MASSA PENCETAKAN BRIKET TERHADAP KARAKTERISTIK PEMBAKARAN BRIKET PADA KOMPOR BIOMASSA - Wangko Iwan Marchel; Pangkerego Freeke; Tooy Dedie (Universitas Sam Ratulangi, 2018)
ABSTRACT This research aims to analyze the differences from the type of material and mass of briquette molding toward the characteristics of burning briquette. Burning characteristics include temperature of burning, burning time, boiling time of water, and thermal efficiency resulting from. The method used in this research is descriptive experimental method with coconut shell and corncob as raw material for briquettes. This study uses the difference in mass of material when molding briquettes. The mass of material at the time of moulding is divided into 50 g and 40 g. The results indicate the quality of briquettes as follows, moisture content of 7.22%-8.31%, density of 0.52 g/cm3 – 0.78 g/cm3, a heat value of 6,259.81 cal/g – 6,906.56 cal/g. Briquettes A (coconut shell with a mass printing of 50 g) produces the lowest moisture content 7.22%, the highest density 0.78 g/cm3, as well as the greatest heating value i.e. 6,906.56 cal/g. The results of the burning indicate optimum fire temperature reached 934.8 oC from briquettes B (coconut shell with a mass printing of 40 g). Average the time of boiling 2 litres of water ranged from 22.16 minutes – 27 minutes with a total of boil water between 12-14 liters, the burning time ranging between 167 minutes/kg – 220 minutes/kg briquettes, as well as thermal efficiency achieved 14.03% – 15.15%. Keywords: Briquette, burning characteristics, thermal efficiency.